Strengthening collaborative learning in secondary school: development and evaluation of a lesson-integrated training approach for transactive communication - Jurkowski, Susanne; Mundelsee, Lukas; Hänze, Martin (Learning and instruction, 2024)
Background - Transactive communication in collaborative learning environments occurs when students refer to their learning partners' ideas, build on them, and transform them into more elaborate ideas. This learning activity is essential for students to be able to benefit from collaboration, but they need scaffolding to produce transactive statements. From the teachers’ perspective, this intervention should take little effort. - Aims - We developed and evaluated a lesson-integrated training in transactive communication for secondary school students, including instructions, exercises, and feedback on transactive communication, materials and tasks on curriculum-related content, and working with various cooperative learning methods. - Sample - In a quasi-experimental pre-test post-test design, 594 ninth-grade students in 23 classes received training in transactive communication or presentation skills. A complete set of data exists for a parallelized sample of 82 students in each condition. - Methods - At both points of measurement, students worked in dyads, and their communication was audiotaped, transcribed, and their transactive statements and non-transactive, content-related externalizations were coded. Furthermore, students completed knowledge tests about the topic of partner work and reported on their experiences with collaboration and motivation for group work (trait). - Results - Analyses revealed positive effects of the training in transactivity on transactive statements and experiences with collaboration. Students with the training in transactive communication also produced more externalizations. However, no differences were found for students’ knowledge acquisition and motivation for group work. - Conclusion - The training in transactive communication was effective for the collaborative working process, but transfer effects need to be further investigated.